O passado é uma parada: um estudo sobre o brega dançado nos Bailes da Saudade em Belém do Pará - NASCIMENTO, Mariana de Fátima Lima do (2018)
This research study about thematic of Brega in Belém of Pará State, emphasizing a peculiar party of this theme, Baile da Saudade, as a locus of research. At this party there are various ballroom dancing, including the Brega rhythm. In this sense, exposes the dynamics of a Baile da Saudade, their dances, their music, their public age group, the brega as one of the most important dances at party, which is produced and reproduced. Thus, it is an overview of the meaning of the word Brega considering the construction and use of the term by citizen of Para state and adepts of Brega culture, as in other states of Brazil. And to understand the Brega dance in Baile da Saudade, this is described in order to know how Brega is skillfully danced by frequenters of these places.